Quantitative Alteration In The Nucleic Acids And Protein During Ovarian Cycle Of Colisa Fasciatus(Bi. & Schn.) , A Tropical Freshwater Perch Under Distillery Effluent Stress - ANURADHA SHUKLA; J.P.SHUKLA (International Journal of Pharma and Bio Sciences, 2012)
Studies were undertaken to record distillery effluent induced quantitative alterations in the nucleic acids (DNA & RNA) and protein during three principal phases of ovarian cycle (prespawning, spawning and post spawning) of Colisa fasciatus , a tropical freshwater fish. Observation were recorded under three different concentrations of the distillery effluent after 30 days of exposure. Observations reveal that 5% effluent concentration could produce least significant alterations (P>0.05) in the nucleic acids and protein content during any phase of ovarian cycle after 30 days of exposure. However, 10% and 20% distillery effluent concentration brought significant alterations in the nucleic acid (DNA & RNA ) as well as protein content in all the phases in ovarian cycle after 30 days of exposure of Colisa fasciatus and was more pronounced under 20% effluent concentration . The declining trend in selected biochemical parameters was more pronounced during the spawning phase in comparison to the preparatory as well as post spawning phase of the ovarian cycle .